2019
DOI: 10.1111/bcp.13935
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus comorbidity in patients enrolled in tuberculosis drug efficacy trials around the world: A systematic review

Abstract: Aims With a prevalence of 16%, diabetes mellitus (DM) is one of the most frequent non‐communicable comorbidities of tuberculosis (TB). DM is a major risk factor for adverse TB outcomes and may require personalized TB drug dosing regimens. However, information on the inclusion of DM in TB drug trials is lacking. We aimed to assess the percentage of recent TB drug efficacy trials that included DM patients. Methods A systematic review was performed and reported according to PRISMA guidelines. PubMed, Science Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…In China, which shoulders a double burden of DM and MDR-TB cases, numbers of patients with DM reached 116.4 million in 2019, ranking first in DM prevalence worldwide [1], while estimated MDR/RR-TB prevalence reached 66,000, ranking second worldwide [2]. Notably, DM is a major risk factor for progression of latent TB to active TB; DM triples future active TB risk and doubles future MDR-TB risk [3][4][5]. Several studies have shown that DM negatively impacts treatment outcomes in patients with MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…In China, which shoulders a double burden of DM and MDR-TB cases, numbers of patients with DM reached 116.4 million in 2019, ranking first in DM prevalence worldwide [1], while estimated MDR/RR-TB prevalence reached 66,000, ranking second worldwide [2]. Notably, DM is a major risk factor for progression of latent TB to active TB; DM triples future active TB risk and doubles future MDR-TB risk [3][4][5]. Several studies have shown that DM negatively impacts treatment outcomes in patients with MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes, Human Immuno deficiency virus and Hepatitis were studied and it shows no statistically significant result to any of the risk factors. Recently study performed in North-East Peninsular Malaysia on the mortality among the Tb and HIV co-morbid patients reported strong relationship on the unsuccessful treatment outcomes of TB and a major risk factor for extra-pulmonary Tb [16]. Present study findings shows only few patients were found to have diabetes which is less than 15 percent of the total diagnosed population with Tb lymphadenitis.…”
Section: Discussionmentioning
confidence: 47%
“…Furthermore, T2D favors more severe manifestations of TB as compared with those occurring in patients without T2D 11 , including extended lung damage especially at chronic stages of the comorbidity 12,13 . Despite this, the evaluation of new treatments or preventive measures against TB in the context of T2D constitutes a poorly explored area 14 , with no report available as of today about the efficacy of protection of any vaccine candidate against TB in the context of T2D.…”
Section: Introductionmentioning
confidence: 99%